2020
DOI: 10.3390/ijerph17092990
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures (PROMs) for Two Implant Placement Techniques in Sinus Region (Bone Graft versus Computer-Aided Implant Surgery): A Randomized Prospective Trial

Abstract: Purpose: To assess patient-reported outcomes measures (PROMs) for two implant placement techniques in cases of sinus bone atrophy (bone graft surgery (BGS) versus computer-aided implant surgery (CAIS)), after surgery and one year later, and to evaluate the clinical success of both treatments. Methods: Sixty patients with bone atrophy in the posterior maxilla and in need of implant placement were randomly assigned to two groups, and in accordance with the case report form (CRF), 30 were treated with BGS and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Patient´s willingness to undergo same type of surgery is essential for future decision-making process. Previous studies have reported that most of the patients indicated willingness to repeat the surgical intervention if needed and would recommend the treatment to friends and relatives following MSFA with autogenous bone graft or a bone substitute alone [ 16 , 18 , 20 ]. These results are in accordance with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient´s willingness to undergo same type of surgery is essential for future decision-making process. Previous studies have reported that most of the patients indicated willingness to repeat the surgical intervention if needed and would recommend the treatment to friends and relatives following MSFA with autogenous bone graft or a bone substitute alone [ 16 , 18 , 20 ]. These results are in accordance with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Patient´s perception of recovery and assessment of OHRQoL in conjunction with MSFA are seldomly reported [15][16][17][18][19][20][21]. Previous studies have indicated that patient´s perception of recovery is influenced by patientrelated predictors, incidence and severity of complications, presurgical expectations, past dental experiences as well as psychological and psychosocial factors [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Patient‐reported outcome measures and OHRQoL reflect psychosocial parameters related to patient's perception of the surgical intervention and recovery including pain, swelling, bruising, inability to eat and sleep, physical appearance, working, and social interaction as well as their self‐esteem and satisfaction with their oral health. Patient's perception of recovery after MSFA have previously been assessed in few studies (Alayan & Ivanovski, 2018; Almahrous et al, 2020; Farina et al, 2018; Mardinger et al, 2009; Younes et al, 2019). Mild‐to‐moderate pain and inability to participate in daily activities for 2 and 3 days have been reported after MSFA with 1:1 mixture of autogenous bone graft harvested from the buccal antrostomy and bone substitute as evaluated by questionnaire, five‐point Likert‐type scale, and VAS (Alayan & Ivanovski, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mild-to-moderate pain and inability to participate in daily activities for 2 and 3 days have been reported after MSFA with 1:1 mixture of autogenous bone graft harvested from the buccal antrostomy and bone substitute as evaluated by questionnaire, five-point Likert-type scale, and VAS (Alayan & Ivanovski, 2018). A weak of mild to moderate pain has been reported by most of the patients after MSFA with an undescribed grafting material as evaluated by four-point Likert-type rating scale and verbal rating scale (Almahrous et al, 2020). All patients were either satisfied or very TA B L E 5 Questionnaire assessing social and working isolation, physical appearance, and quality of life alterations, at 1 week satisfied with the treatment outcome and 92% would recommend the treatment, after 1 year (Almahrous et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation